Characterization of salt tolerant wheat genotypes by using morpho-physiological, biochemical, and molecular analysis - Irshad, Ahsan; Ahmed, Rana Imtiaz; Ur Rehman, Shoaib; Sun, Guozhong; Ahmad, Furqan; Sher, Muhammad Ali; Aslam, Muhammad Zahid; Hassan, Mohamed M.; Qari, Sameer H.; Aziz, Muhammad Kashif; Khan, Zulqurnain (Frontiers in Plant Science, 2022)
Salinity mostly occurs in arid and semi-arid regions. It causes many adverse physiological effects on plant such as toxic ion accumulation, osmotic potential, photosynthetic rate, and yield, thus resulted in huge economic loss. The aim of the present study was to investigate morphological, physiological, biochemical, and genetic parameters of wheat genotypes under salt stress. Two experiments were carried out on six wheat varieties, the earlier was to assess the salt tolerance at seedling stage while the lateral to determine the effect of salt stress on these six wheat varieties at maturity stage. Seeds were sown at 0mM and 150mM of salinity level. Biochemical traits i.e., shoot/root fresh and dry weight, chlorophyll a/b and total chlorophyll contents, shoot nitrogen, shoot phosphorus, proline, and carbohydrates were measured. Wheat varieties showed significant increase in free amino acids, shoot nitrogen, and total soluble proteins under saline conditions. Higher Na+/K+ ratio, and free amino acids were estimated under 150mM NaCl treatment in Pasban-90 and found to be the most salt-tolerant cultivar. By contrast, reduced proline, total chlorophyll and Na+/K+ ratio was found in Kohistan-97 marked it to be sensitive to the stress. Expression analysis of HKTs genes were performed to validate the results of two contrasting varieties. The differential expression of HKT2;1 and HKT2;3 explained the tissue and genotype specific epigenetic variations.